Production and characterization of green algae biomass for the application of mild steel corrosion protection - Khanra A.; Vasistha S.; Prakash Rai M.; Prakash R. (My University, 2025)
Metal corrosion inhibition by incorporating green biomass has prompted the researchers for exploring toward the sustainable and economical approach. Green inhibitors attained from various plant extracts have widely been applied to prevent the metal corrosion under acidic environment. Hence, the plant-derived green inhibitors are to be served as one of the possible substitutes of synthetic products. However, despite of having eco-friendly and nontoxic behavior of plant-based bio-products, a predicament still continue in food-based products, which introduces the major bottleneck for commercial purpose. Hence, it is necessary to find an economical inhibitor for metallic corrosion resistance. Oxygenic photosynthetic microalgae have wide distribution in freshwater as well as marine habitat. As microalgae are having plentiful and ample source for oil accumulation, thereby, microalgae oil is introduced firstly to reveal the anticorrosion ability of mild steel (MS) in acidic environment. Microalgae oil has been constituted with mainly triglycerides, saturated and unsaturated free fatty acids, fatty acid methyl esters (FAME), fatty alcohols, etc. The chain length arrangement of algae-derived oil facilitates a pivotal role to assign the specific oleochemical applications. Long aliphatic chains FAMEs, comprising 12–18 carbons have preferably been utilized for biodiesel synthesis, and 18–22 carbon atoms are consumed as lubricants. Hence, oil from green microalgae has been anticipated to enhance the anticorrosion potency to produce self-assembled adsorptive layers onto MS in acid solution via physical adsorption. © 2023 Elsevier Inc. All rights reserved.